Information as a source of anxiety in organizations - Filho, Roberto Cavallari; Ribeiro, Karla Cristina Rocha; Jorge, Carlos Francisco Bitencourt [UNESP]; Rodrigues, Raphael Zanon [UNESP]; de Oliveira, Gabriela Balarin; Martins, Daisy Souza; Maranho, Beatriz Cristina; Otre, Maria Alice Campagnoli; de Oliveira, Bruno Bastos (My University, 2020)
The purpose of the study was to identify the impact of information in the context of knowledge creation among workers from startup enterprises. Based on observation of the current scenario of organizations, we analyzed the fact that information may modify the behavior of subjects in different ways. Thus, while we should consider information as a resource for organizations, we should also understand its impact on workers' general health in terms of a feeling of inability to grasp multiple information in the process of knowledge production. Among other problems, somatic diseases and the burnout syndrome interfere with mental and physical health. Given this scenario, the study aimed to understand the information behavior of knowledge workers in the new enterprises. To achieve this goal, the case study method was applied, which included the use of triangulation, i.e. different data collection and analysis techniques contributing greater consistency to the study when validating the data and the analysis performed. The study population was 18 subjects from 4 different information technology companies classified as startups. With the information collected, parameters could be constructed on the basis of the people management strategies developed by Ribeiro et al (2019), capable as they are of minimizing the impact of information anxiety among workers from these new enterprises.
La información como un recurso de ansiedad en las organizaciones
O impacto da ansiedade em informação nas startups de inovação
Keywords: Information anxiety; Information behavior; Innovation; Knowledge workers; People management; Startup